(untitled) (Acta Polytechnica CTU Proceedings, 2017)
This paper is dealing with improving the railway transport on axis Decín – Rumburk. This journey can be undertaken in two possible ways (as an interstate one or an international one through Germany), however the connections between trains are limited (especially problematic is the Rumburk junction, where the connection would be desired). The aim of this paper is to improve the connections in the whole area, in order to reach the maximal effectiveness of a railway passenger transport.